Field therapies for actinic keratosis: an Australian cost‐effectiveness analysis - Yaron Gu; Kinar Mistry Shah; Grace Xiaoying Li; Deshan Frank Sebaratnam; Helen Yiling Sun (JEADV Clinical Practice)
Abstract Background Actinic keratoses have a high prevalence in the older Australian population, with most patients presenting with field actinic damage. Despite this high prevalence, no field therapies are subsidised under the Pharmaceutical Benefits Scheme. Objectives To determine which therapy for field actinic damage is the most cost‐effective when comparing 5‐fluorouracil (5‐FU), imiquimod (IMQ), and methyl‐aminolevulinate photodynamic therapy (MAL‐PDT) at 12 months post‐treatment. Methods A decision tree was constructed using TreeAge Pro, representing the likely clinical trajectories of patients with field actinic damage treated with 5‐FU, IMQ, and MAL‐PDT. The cost‐effectiveness analysis was performed from the patient perspective, assuming an outpatient setting. Efficacy data was derived from a single‐blinded, multi‐centre prospective randomised control trial. Cost data were derived from Australian dermatology clinics and pharmacies. One‐way and probabilistic sensitivity analyses were conducted. Results 5‐FU was the most cost‐effective treatment. It was cheaper and more effective than all other treatments, with a cost‐effectiveness ratio of AU$201 per patient achieving ≥75% clearance in field actinic damage. The cost‐effectiveness ratios of IMQ, and MAL‐PDT were AU$940, and AU$8058 per patient achieving ≥75% clearance respectively. Both sensitivity analyses showed certainty in 5‐FU's dominance over the other treatments. Conclusions 5‐FU is the most cost‐effective treatment option for Australian patients presenting with actinic field damage on the head area.